-2x-7+6(x+1)=-3x-6

Simple and best practice solution for -2x-7+6(x+1)=-3x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x-7+6(x+1)=-3x-6 equation:


Simplifying
-2x + -7 + 6(x + 1) = -3x + -6

Reorder the terms:
-2x + -7 + 6(1 + x) = -3x + -6
-2x + -7 + (1 * 6 + x * 6) = -3x + -6
-2x + -7 + (6 + 6x) = -3x + -6

Reorder the terms:
-7 + 6 + -2x + 6x = -3x + -6

Combine like terms: -7 + 6 = -1
-1 + -2x + 6x = -3x + -6

Combine like terms: -2x + 6x = 4x
-1 + 4x = -3x + -6

Reorder the terms:
-1 + 4x = -6 + -3x

Solving
-1 + 4x = -6 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-1 + 4x + 3x = -6 + -3x + 3x

Combine like terms: 4x + 3x = 7x
-1 + 7x = -6 + -3x + 3x

Combine like terms: -3x + 3x = 0
-1 + 7x = -6 + 0
-1 + 7x = -6

Add '1' to each side of the equation.
-1 + 1 + 7x = -6 + 1

Combine like terms: -1 + 1 = 0
0 + 7x = -6 + 1
7x = -6 + 1

Combine like terms: -6 + 1 = -5
7x = -5

Divide each side by '7'.
x = -0.7142857143

Simplifying
x = -0.7142857143

See similar equations:

| X-2+x-3=57 | | 15.2d+7.24=-2.6-2.3d+11.59 | | 5(x-4)+6x=3(1-x) | | -9-3x=-5x+9 | | 1w-4=9-1w | | X+x=22+6 | | 28p=6p^2 | | .65X=9.10 | | 4-10k=34 | | x=4*60-160 | | 5+7(2x+11)+4x= | | 3x-6+8x=2x-3 | | W-4=9-w | | f(x)=-11x+3 | | 7x-7=4(2x-3) | | 12-12y-3(y+2)=4y+6-y | | x^3+40=13 | | 5e^9t=7e^8t | | 9+6=135 | | 2x+(-7+1x)=-1 | | 3x(x+2)=-18 | | -2(y+2)=3y | | 7s-8=64 | | y=17x^3 | | -14-8-6c=12-4c | | x=.25*150+40 | | 15-4(x+3)=19 | | 0.6h=13.032 | | 8s-8=65 | | Logx=.75 | | 5x-5+4x=-41 | | 3x+(x-5)=-11 |

Equations solver categories